Foam Properties Of Bahulu Batter As Influenced By Stabilizers - Jalaludin, Nurul Syafira Nabila (Universiti Sains Malaysia, 2021)
The formation and stability of foams and emulsions in Bahulu cake batter is a critical quality criterion in ensuring the quality of the final product such as structure, tenderness, moisture, and flavour Especially in the food industry, where consumer perceptions of quality are heavily impacted by appearance In this study, Gum Arabic (GA) and Carboxymethylcellulose (CMC) was selected as stabilizers with same levels of concentration (0.25%, 0.50%,0.75%,1.0%) to incorporated into Bahulu to study the effect on stabilization and quality of foam. Tests on viscosity, pH, overrun measurement and density were performed on all samples. Viscosity of batter with GA decreased significantly due to the contribution to low molecular weight compared to CMC resulting in low surface tension. In this experiment found, molecular weight in both stabilizers are related to viscosity whereby it indicates that batter have tendency to adsorb at air- water surface emulsion. The density of batter with CMC increased significantly compared to GA due to incorporation of air which decreases the density and modified batter viscosity. The more the air incorporated during whipping, the more the foam density to reduce whipping ability to increase.